Über einige Prosodes-Arten aus Mittelasien (Coleoptera: Tenebrionidae). - Skopin, N. G. (Contributions to Entomology = Beiträge zur Entomologie, 1971)
As the result of his examination of some types of the genus Prosodes in the collection of the former Deutsches Entomologisches Institut, chiefly described by Kraatz from Central Asia, the author gives his opion on the labelling of the types and the series of types. He mentions the synonymy of some of the species under consideration and describes some new species and intraspecific forms.Nomenclatural Actsalaiensis Kraatz, 1885 (Prosodes), Lectotypeballionis Kraatz, 1885 (Prosodes), Lectotypebrevitarsis Kraatz, 1882 (Prosodes), Lectotypecatenulata Kraatz, 1883 (Prosodes), Lectotypecostifera Kraatz, 1886 (Prosodes), Lectotypediloides Kraatz, 1882 (Prosodes), Lectotypegrandicollis Kraatz, 1883 (Prosodes), Lectotypeheydeni Kraatz, 1882 (Prosodes), Lectotypelongicornis Kraatz, 1883 (Prosodes), Lectotypeminima Kraatz, 1882 (Prosodes), Lectotype now a synonym of Prosodes pygmaeaminuta Kraatz, 1881 (Prosodes), Lectotypepseudalaiensis Skopin, 1971 (Prosodes), spec. n.pygmaea Kraatz, 1882 (Prosodes), Lectotypepygmaea kelessiana Skopin, 1971 (Prosodes), ssp. nov.rugosicollis Kraatz, 1885 (Prosodes), Lectotypestaudingeri Kraatz, 1882 (Prosodes), Lectotypeacutimarga Skopin, 1971 (Prosodes costifera), sspec. n.padshaatinus Skopin, 1971 (Prosodes rugosicollis), sspec. n.sarytshelekis Skopin, 1971 (Prosodes rugosicollis), sspec. n.